Evaluating Estimated Dose outside the Patients Undergoing Myocardial Perfusion Imaging with 99mTc-MIBI - amir reza khorasanchi; Esmat Ramezanzadeh; Azam eskandari; Erfan saatchian; mahmoodreza yahyaei (Iranian Journal of Medical Physics, 2023)
Introduction: It is important that estimated doses from patients administered radiopharmaceuticals in nuclear medicine by hospital staff but other people in connection to patients need radiation protection. The purpose of this study was to measure the dose rate with increasing distance from patients to estimate the average effective dose in hospital staff and companions of patients. Material and Methods: Myocardial perfusion scanning was performed using Technetium 99m-methoxy isobutyl isonitrile (99mTc-MIBI) (in 2 groups of stress and rest). We measured the external dose rate for 48 patients (23 men and 25 women) at 4 distances and 5 times. Doses are estimated for a range of scenarios, in hospital staff, public transportation, and family contacts. Finally, the obtained data were compared to the trigger level introduced by the International Commission on Radiological Protection 53 and 62 (ICRP). Data analysis was performed using SPSS version 24. Results: The distance of the times when patients need family or hospital staff to be with them was divided into 4 categories (injection to scanning, using public transport, emergency patients during injection to scanning, and emergency patients after finishing medical procedures). Conclusion: In all scenarios, effective doses were obtained at less than 100 µSv according to ICRP guidelines. Due to the significant increase of the uptake in the heart and skeleton, after injection, the dose rate per MBq in the stress rate before 1hr decreases more slowly than the rest test, and the effective dose of hospital staff in stress procedure is more than rest procedure.